Phylogenetic relationships of corbiculate bees (Hymenoptera: Apidae: Apini) - Porto, Diego Sasso (2015)
Bees are aculeate hymenopterans, which, altogether, comprise approximately 20,000 valid species divided into seven families, among which Apidae is one of the best known groups. In addition to the species richness, a remarkable diversity of social behaviors is known to exist within this group, ranging from strict solitary taxa (over 80% of bee species) to groups showing highly sophisticated behaviors related to life in society. One of the most fascinating groups of bees in this respect is that of corbiculate bees (Apidae: Apinae: Apini). Amongst its four subtribes, Apina and Meliponina comprise the so-called \"fixed-caste eusocial\" groups. Phylogenetic relationships of corbiculate bees have been under intense controversy for the last two decades, thus hampering a robust understanding of the evolution of eusocial traits. Most hypotheses based on morphological/behavioral data point to a clade uniting Apina + Meliponina, thus favoring a single origin scenario for the evolution of fixed-caste eusociality. Molecular datasets, on the other hand, consistently indicated independent origins for this cluster of traits. In this contribution, the main goal was to re-evaluate the phylogenetic relationships between the major lineages of corbiculate bees exploring new sources of information from internal skeletal structures of exoskeleton. It were provided descriptions/discussions on some important morphological complexes of the head capsule, mandibles, sitophore, propectus, meso/metafurca and mesophragma of bees. Also, it was attempted to standardize the current morphological terminology used for bees to that used for other Hymenoptera. A set of different phylogenetic analysis with the main lineages of Apidae emphasizing the corbiculate clade was conducted. The complete morphological matrix with 93 characters from external morphology and 42 from internal structures of exoskeleton resulted into two most parsimonious trees with 376 steps, CI=45 and RI=78, which were congruent with the current morphological/behavioral scenario for the corbiculate relationships: Euglossina + (Bombina + (Apina + Meliponina)). It was demonstrated that characters extracted from internal structures of exoskeleton, although poorly explored, can provide critical evidence to elucidate the corbiculate controversy. Moreover, despite the inclusion of new sources of data is fundamental to elucidate this issue, some efforts should be made to reevaluate many characters currently in (re)use. Also, the inclusion of fossil information and use of new technologies for phenotypic studies can open new windows for future comparative morphological studies in bees